Account Representative (Ar) Service Quality And Tax Awareness On Taxpayer Compliance - Herry Aprilia Manubulu; Nussin Hendrik Tael (Jurnal Mantik, 2022)
This study aims to examine the effect of Account Representative (AR) service quality and tax awareness on taxpayer compliance. By using the method of distributing questionnaires to individual taxpayers and corporate taxpayers with incidental sampling technique. The results of this study indicate that the quality of Account Representative (AR) service and tax awareness have a positive effect on taxpayer compliance. Taxpayer compliance will increase if the quality of service provided by the Account Representative is more focused and consistent as well as a high awareness of the taxpayer to continue to carry out tax obligations in an orderly manner